2003
DOI: 10.1097/00129492-200305000-00013
|View full text |Cite
|
Sign up to set email alerts
|

A Middle Ear Implant, the Symphonix Vibrant Soundbridge: Retrospective Study of the First 125 Patients Implanted in France

Abstract: The results indicate a high level of satisfaction with the VSB as a treatment of sensorineural hearing impairment in patients with a wide range of characteristics. Preoperative scores for unaided speech comprehension tests in quiet may be a potential indicator of success on aided Vibrant Soundbridge speech comprehension tests postoperatively but do not reflect patient satisfaction with the device reported on self-assessment scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
95
2
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 13 publications
12
95
2
9
Order By: Relevance
“…This group of patients had tried conventional amplification in the form of analogue or digital HAs but cited the following reasons for dissatisfaction with them: insufficient benefit (83%), cosmetic issues (83%), poor sound quality (67%), feedback (50%), and harshness of sounds. Similarly, in 125 patients aged 24-81 years (mean = 56) consecutively implanted with the VSB, Sterkers et al [29] found significantly increased speech understanding in quiet and found most patients (83%) were either satisfied or very satisfied with the VSB.…”
Section: Active Middle Ear Implantsmentioning
confidence: 97%
“…This group of patients had tried conventional amplification in the form of analogue or digital HAs but cited the following reasons for dissatisfaction with them: insufficient benefit (83%), cosmetic issues (83%), poor sound quality (67%), feedback (50%), and harshness of sounds. Similarly, in 125 patients aged 24-81 years (mean = 56) consecutively implanted with the VSB, Sterkers et al [29] found significantly increased speech understanding in quiet and found most patients (83%) were either satisfied or very satisfied with the VSB.…”
Section: Active Middle Ear Implantsmentioning
confidence: 97%
“…Their short-and long-term efficacy and safety is now established [Sterkers et al, 2003;Vincent et al, 2004;Mosnier et al, 2008]. Based on these data, and the ability of these devices to deliver amplified sound energy in the middle ear, the idea of placing the transducer close to the cochlea in case of abnormal middle ear emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, active middle ear implants (AMEI) have been developed to overcome these problems [Kasic and Fredrickson, 2001;Jenkins et al, 2004Jenkins et al, , 2007Jenkins et al, , 2008. The floating mass transducer of the Vibrant Soundbridge from Med-El (Innsbruck, Austria), the Middle Ear Transducer TM from Otologics LLC (Boulder, Colo., USA) and the Esteem 2 (Envoy Medical, St. Paul, Minn., USA) are three commercially available AMEI for the treatment of moderate-to-severe sensorineural hearing loss in adults [Kasic and Fredrickson, 2001;Sterkers et al, 2003;Jenkins et al, 2004Jenkins et al, , 2007Jenkins et al, , 2008; Barbara et al, 2009]. Some of these devices have been applied in conductive or mixed hearing loss therapy [Colletti et al, 2006;Siegert et al, 2007;Venail et al, 2007;Hüttenbrink et al, 2008;Tringali et al, 2008Tringali et al, , 2009Beltrame et al, 2009;Lefebvre et al, 2009;Martin et al, 2009] but none are currently FDA approved for this application.…”
Section: Introductionmentioning
confidence: 99%